A Stable Flexible Silicon Nanowire Array as Anode for High-Performance Lithium-ion Batteries. (10th September 2015) - Wang, Jiantao; Wang, Hui; Zhang, Bingchang; Wang, Yao; Lu, Shigang; Zhang, Xiaohong
Highlights: A flexible SiNW array in PDMS structure is designed and fabricated as Li-ion battery anode material. The aggregation and fracture of SiNWs are alleviated by the flexible PDMS skeleton during the process of charge and discharge. The loose SiO2 shells coating on the SiNWscould form the protective layer in charge/discharge. The as-obtain flexible SiNW array/PDMS composite exhibits a much better cycling stability. Abstract: A Silicon nanowire (SiNW) array inserted into flexible poly-dimethylsiloxane (SiNW array/PDMS) composite structure as anode with high capacity and long-term cycling stability is synthesized by a cost-effective and scalable method. In this structure, the aggregation and fracture of SiNWs are alleviated by the flexible PDMS skeleton. Act as the main active component, the SiNWs are coated by loose SiO2 shells. These loose SiO2 shells not only provide space for the large volume changes of SiNW, but also react with the electrolyte and form the stable protective layer during the processes of the lithiation and delithiation. These two functions could improve the cycling stability and columbic efficiency of the SiNWs. The as-obtain flexible SiNW array/PDMS composite structure exhibits excellent long-term cycling stability with a specific capacity of 887.2 mA·h·g −1 and capacity retention of ∼83.4% over 350 cycles at 0.5 C rate compared with the fifteenth cycle. The design of this new structure provides a potential way for developing other functional composite materials.